Advancing Women Entrepreneurs: A Framework for Small Family Businesses Success within the Sustainable Economy - Xuan, Liew Mei; Jamaluddin, Askiah; Zainalaludin, Zumilah; Yusoff, Irwan Syah Md. (STIE Malangkucecwara, 2024)
This article introduces the Holistic Enterprise Success and Sustainability Index (HESSI), a novel framework designed to enhance the success of women-led small family businesses (SFBs) in the context of a sustainable economy. Through a comprehensive literature review and theoretical exploration, this study articulates how women entrepreneurs' perspectives are intricately aligned with both familial values and business imperatives. HESSI employs a robust suite of indicators to measure financial robustness, societal contribution, environmental stewardship, and family solidarity—each meticulously refined to reflect the specificities of women-led SFBs. These indicators transcend traditional, financial-centric metrics, advocating for an expansive evaluation of success that considers economic performance alongside social, environmental, and familial well-being. Crucially, the HESSI framework incorporates women's familial insights, positioning them as a driver of internal cohesion and a pivotal element in integrating Environmental, Social, and Governance (ESG) principles. This broader vision of success metrics includes family unity and the perpetuation of legacy. HESSI promotes an all-encompassing approach to success evaluation that is grounded in gender perspectives, entrepreneurial agility, and a staunch commitment to sustainability principles. The discourse presented is a significant contribution to the fields of gender, entrepreneurship, and sustainable development, providing actionable insights into the vital role of women entrepreneurs in forwarding the sustainability agenda. It underscores the importance of advancing education, reinforcing policy frameworks, and fostering community solidarity to support and extend the reach of women-led SFBs, thus charting a course towards a more equitable and sustainable future in the business landscape.